Organic foods: Consumer habits and commercialization strategies in Sorocaba in the state of São Paulo, Brazil - Buquera, Rodrigo Brezolin; Marques, Paulo Eduardo Moruzzi; Franco, Fernando Silveira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Despite the growth of the organic food market in Brazil, these foods remain restricted to a minor part of the population. In this scenario, the short circuits are presented as an alternative to the predominant food distribution model, which is characterized by impersonality and long distances. This paper aims to analyze the motivation of the organic products consumers and this market in Sorocaba (in the state of São Paulo). For this purpose, two methodological procedures were used: an online survey (quantitative approach) and semi-structured interviews (qualitative approach). As results, the consumers habits revealed two different positions: an appreciation of practicality and a search for diversity, both in products and in ways of purchasing them. Because of these choices the consumers alternate between short and long circuits possibilities.